Nocturnal pollinatIon by Fungus gnats of the colombian endemic species, Pleurothallis marthae (orchidaceae: pleurothallidinae) - Duque Buitrago, Carol Andrea (Universidad de Costa Rica, 2014)
Contemporary patterns of plant biodiversity result from the ecological and evolutionary processes generated by species interactions. Understanding these interactions is key for effective biodiversity conservation at the species and the ecosystem level. Orchid species often have highly specialised pollinator interactions, and the preservation of these is critical for in situ orchid conservation. The majority of orchid species occur in tropical regions, and information regarding their interactions is limited. We present data on pollinator identities, pollination mechanisms and flowering phenology of the Colombian endemic orchid, Pleurothallis marthae. We evaluated the mechanisms of attraction, the presence of osmophores, and the reproductive system of the species. Pleurothallis marthae is self-compatible with nocturnal anthesis pollinated by Mycetophila sp. (Mycetophilidae), probably attracted by a string fungus like smell liberated by the flower and Bradysia sp. (Sciaridae) that feed on nectar in the labellum. Osmophores and nectaries were detected in the epidermis of the sepals and petals. We present new evidence that the genus Pleurothallis is adapted to Diptera pollination. Our study indicates that the pollination mechanism of P. marthae is based on the nocturnal attraction of two species of fungus gnats, probably combining food attraction and brood place deception